Effect of Ni Nanoprticles Coating on the Oxidation Behaviour of Carbon Fibers - Lu, X.X.; Lu, C.X.; Yang, Y.; He, F. (Asian Journal of Chemistry, 2012)
Carbon fibers with nickel nanoparticles coating were prepared by continuously electroplating. On the basis of thermal analysis of the samples with different nickel weight gain, it was found that the weight of nickel coating affected the oxidation behaviour of carbon fibers: when carbon fibers were coated with 2 wt % Ni, Ni nanoparticles catalyzed the oxidation of carbon fibers. On the contrary, when carbon fibers were coated with 25 wt % nickel, nickel coating protected carbon fibers, resulting in better oxidation resistance of carbon fibers.